Migration and Performance in Contemporary Ireland - McIvor, Charlotte. author. aut Link
XIII, 296 p. 7 illus. in color.
Keywords: This book investigates Ireland’s translation of interculturalism as social policy into aesthetic practice and situates the wider implications of this ‘new interculturalism’ for theatre and performance studies at large. Offering the first full-length, post-1990s study of the effect of large-scale immigration and interculturalism as social policy on Irish theatre and performance, McIvor argues that inward-migration changes most of what can be assumed about Irish theatre and performance and its relationship to national identity. By using case studies that include theatre, dance, photography, and activist actions, this book works through major debates over aesthetic interculturalism in theatre and performance studies post-1970s and analyses Irish social interculturalism in a contemporary European social and cultural policy context. Drawing together the work of professional and community practitioners who frequently identify as both artists and activists, Migration and Performance in Contemporary Ireland proposes a new paradigm for the study of Irish theatre and performance while contributing to the wider investigation of migration and performance. .